Development and application of the TFA macrosimulation model: a case study of modelling the impact of trans fatty acid (TFA) elimination policies in Brazil - Eduardo Augusto Fernandes Nilson; Neha Khandpur; Fabio da Silva Gomes (BMC, 2022)
Abstract Introduction The consumption of trans-fatty acids (TFA) is directly associated with cardiovascular disease risk and is responsible for a significant health burden globally. The policy strategies for reducing TFA include limiting their content in foods and eliminating partially hydrogenated oils (PHO) in the market. This study aims to describe a comparative risk assessment macrosimulation model and to apply this tool to estimate the potential reductions in CVD mortality gained from the compared scenarios of TFA reduction/elimination in Brazil. Methodology We developed and implemented a comparative risk assessment macrosimulation model estimates the potential CVD mortality reduction (coronary heart disease - CHD- and stroke) if TFA intake is reduced in diets. The TFA macrosimulation model estimates the change in the annual number of NCD deaths between baseline with current TFA consumption levels and alternate or counterfactual scenarios, such as considering different limits to TFA content in foods and the elimination of PHO in Brazil in 2018. The model incorporated additional outputs related to other impacts of TFA reduction on DPP, such as Years of Life Lost, Years of Productive Life Lost, and related economic impacts of premature deaths. Results In 2018, a 2% limit for TFA in the oils and fats and a 5% limit of TFAs for other foods could avert or postpone approximately 2,000 deaths (UI 95% 1,899-2,142) and save US$ 32.1 million savings in productivity losses to the economy associated to premature deaths. An intermediate scenario, applying a 2% limit of TFA in all food products In Brazil could prevent or postpone approximately 6,300 deaths (UI 95% 5,925-6,684) and the premature deaths prevented would represent US$ 100.2 million in economic saving. Finally, by banning PHO, approximately 10,500 deaths could be prevented or postponed (UI 95% 9,963 − 10,909), corresponding to US$ 166.7 million in savings to the economy because of premature deaths. Conclusion The TFA macrosimulation model can efficiently compare different policy scenarios for trans fats reduction policies at the country level and proves that the elimination of PHOs from the food market in Brazil may significantly reduce the health burden of trans fatty acids in the country compared to other policy options. The model also represents a useful public health tool to support TFA reduction and elimination policies in other countries.